The Levelized Cost of Storage of Electrochemical Energy Storage Technologies in China - Xu, Yan; Pei, Jiamei; Cui, Liang; Liu, Pingkuo; Ma, Tianjiao (Frontiers in Energy Research, 2022)
Large-scale electrochemical energy storage (EES) can contribute to renewable energy adoption and ensure the stability of electricity systems under high penetration of renewable energy. However, the commercialization of the EES industry is largely encumbered by its cost; therefore, this paper studied the technical characteristics and economic analysis of EES and presents a detailed analysis of the levelized cost of storage (LCOS) for different EES technologies. The results show that the LCOS of lead carbon (12 MW power and 24 MWh capacity) is 0.84 CNY/kWh, that of lithium iron phosphate (60 MW power and 240 MWh capacity) is 0.94 CNY/kWh, and that of the vanadium redox flow (200 MW power and 800 MWh capacity) is 1.21 CNY/kWh. A detailed analysis of the cost breakdown showed that the proportion of the Capex and charging costs of EES projects are relatively high, while the Opex and tax costs are comparatively low. The difference between EES projects is the proportion of replacement costs. Finally, a sensitivity analysis considering four factors is presented, with this paper considering the impact of round-trip efficiency, storage duration, unit initial investment, and storage application scenario on the LCOS of EES.